Arang Aktif Ampas Tebu Termodifikasi Kitosan sebagai Adsorben Tetrasiklin: Pemanfaatan Metode Kolom: Chitosan Modified Sugarcane Bagasse Activated Charcoal as Tetracycline Adsorbent: Utilization of the Column Method - Gatut Ari Wardani; Adinda Nur Octavia; Mochamad Fathurohman; Taufik Hidayat; Estin Nofiyanti (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Currently, antibiotics are considered environmental pollutants because of their undesirable effects on human health and the environment, including the waste of antibiotics tetracycline hydrochloride. While on the other hand, bagasse is an agricultural waste that has no economic value. This study aims to study the characteristics of activated charcoal from bagasse and the use of bagasse as chitosan-modified activated charcoal using the column method to determine the variation of adsorbent height, flow rate, and acidity of the solution in the ability of the bagasse adsorbent to adsorb tetracycline hydrochloride. Bagasse goes through a carbonation process using a furnace at a temperature of 350°C until charcoal is formed. The next process is activation using 2 M phosphoric acids and compared based on SNI 06-3730-1995 regarding technically activated charcoal. Determination of functional groups using Fourier Transform Infra-Red, adsorbent morphology using Scanning Electron Microscope, and crystallinity using X-Ray Diffraction. The concentration of tetracycline hydrochloride before and after adsorption was measured using an Ultra Violet-Visible spectrophotometer. The best absorption results in the adsorption process were found at the adsorbent height of 14 cm (99%), the flow rate of 0.5mL/minute (92%), and pH 4 (93%).